(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article presents opinions on the role and importance of ecommerce in the digital economy of our country, the stages of its development andopportunities for further development. An assessment of its capabilities and determination of development prospects are also highlighted.